Bibliography of Kauṭilīya Arthaśāstra - Sternbach, Ludwik (Vishveshvaranand Vedic Research Institute publication ;, 1973)
Bibliography on the 4th century B.C. treatise on Indian statecraft and social theory, by Kauṭalya.